المسؤولية القانونية الناشئة عن إصابات اللاعبين وتعاطى المنشطات الرياضية: دراسة مقارنة - عثمان، أيمن محمد زين (جامعة الإسكندرية - كلية الحقوق, 2016)
توصلت في هذا البحث لجملة من التوصيات أبرزها ضرورة سن قانون رياضي خاص بالمعاملات الرياضية، بحيث يكون له قدرة على التفاعل مع قضايا الرياضيين، حيث أن قواعد قوانين العمل المهني لا يتناسب تطبيقها على حكم نشاط مثل النشاط الرياضي لعدد من الاعتبارات أوردتها في البحث.
The research , addressing the subject of legal liability arising out of the lighting aspect of legal protection for the player sports aresuit of being injured while practicing for training or competitive match, has 'v analyzed the concept of athelete the quality of professional and amateur, and concluded that players contract with his club sports not only a form of employment contract ,but is charaterized by the specificlity of excellence for professional work and through the jurisprudence and judicial verdict in this area is important and vital. Concentrated study also shed light on the throw of the legal liability arising from the doping genuine danger threatens the health and safety of the athlete as atonic of the role of anegative in terms of harming legitimate competition in the filed of sports which do not accept such behavior.
Keywords: إصابات الملاعب -- الإصابة الرياضية -- المسؤولية المدنية -- المسؤولية القانونية -- المنشطات الرياضية -- عقد اللاعب الرياضى